Early Bortezomib Therapy for Refractory Anti-NMDA Receptor Encephalitis - Turnbull, Marion T.; Siegel, Jason L.; Becker, Tara L.; Stephens, Alana J.; Lopez-Chiriboga, A. Sebastian; Freeman, William D. (Frontiers in Neurology, 2020)
Introduction: Anti-N-methyl-D-aspartate (NMDA) receptor encephalitis is an increasingly recognized form of immune-mediated encephalitis. Here we present a case that represents the shortest hospitalization-to-bortezomib treatment timeline (42 days), and we believe that this is reflected in the patient's outcome with complete independence within a short timeframe. Case Report: We describe a case of anti-NMDA receptor encephalitis in an 18-year-old African American female presenting with progressive, medically refractory disease. Despite two rounds of high-dose intravenous steroids, plasma exchange, immunoglobulin administration, and rituximab for B-cell depletion, the patient failed to respond by hospital day 42 and received off-label use of the proteasome inhibitor bortezomib. During the 15 days after the bortezomib administration, the patient showed dramatic neurologic recovery that allowed her transfer out of the intensive care unit. At follow-up after 1-month, the patient reported feeling normal cognitively and showed dramatic improvement in cognitive scores. Conclusion: This case and literature review provide preliminary evidence that early treatment of anti-NMDA receptor encephalitis with the proteasome inhibitor bortezomib appears safe and tolerable. However, randomized trials are needed to show the efficacy and the long-term benefit.